Pengaruh Asam Humat dan Pupuk P Terhadap Pertumbuhan Tanaman Kacang Panjang (Vigna sinensis L.) - Hendi Ramanda Dalimunthe; Dini Mufriah; Syahriandi Akbari (JURNAL AGROPLASMA, 2026)
Long beans (Vigna sinensis L.) are a horticultural commodity that has great potential to be developed in Indonesia because it is in great demand and has a fairly high economic value. The purpose of this research is to 1. determine the effect of humic acid fertilizer and SP-36 fertilizer and the interaction of the two treatments on the growth of long beans (Vigna sinensis L.). This research will be carried out in the research area located at Jalan Gunung Bendahara 10, South Binjai District, Binjai City. This research was conducted in May to June 2025. This research was conducted using a Factorial Randomized Block Design (RAK) with 2 (two) treatment factors, namely factor I, namely humic acid consisting of 3 (two) treatment levels, namely H0: dose 0 L / ha (without humic acid) (Control), H1: dose 30 L / ha (3 ml / plant), H2: dose 60 L / ha (6 ml / plant), Factor II, namely P fertilizer (SP-36) consisting of 3 (three) treatment levels, namely S0: 0 g / plant (Control), S1: 0.6 g / plant, S2: 1.2 g / plant. The parameters observed include plant height and flowering age. The results of the study showed a significant effect on the treatment of humic acid fertilizer on the growth of long bean plants (Vigna sinensis L). There was a significant effect on P fertilizer (SP-36) on the growth of long bean plants (Vigna sinensis L). There was a significant interaction effect between humic acid and P fertilizer (SP-36) treatments on the growth of long beans (Vigna sinensis L.).Keywords: Long beans, SP36 fertilizer, humic acid